Blocking autofluorescence in brain tissues affected by ischemic stroke, hemorrhagic stroke, or traumatic brain injury - Shaoshuai Wang; Shaoshuai Wang; Xiuhua Ren; Junmin Wang; Qinfeng Peng; Xiaoyu Niu; Chunhua Song; Changsheng Li; Chao Jiang; Weidong Zang; Marietta Zille; Xiaochong Fan; et al. (Frontiers in Immunology, 2023)
Autofluorescence is frequently observed in animal tissues, interfering with an experimental analysis and leading to inaccurate results. Sudan black B (SBB) is a staining dye widely used in histological studies to eliminate autofluorescence. In this study, our objective was to characterize brain tissue autofluorescence present in three models of acute brain injury, including collagenase-induced intracerebral hemorrhage (ICH), traumatic brain injury (TBI), and middle cerebral artery occlusion, and to establish a simple method to block autofluorescence effectively. Using fluorescence microscopy, we examined autofluorescence in brain sections affected by ICH and TBI. In addition, we optimized a protocol to block autofluorescence with SBB pretreatment and evaluated the reduction in fluorescence intensity. Compared to untreated, pretreatment with SBB reduced brain tissue autofluorescence in the ICH model by 73.68% (FITC), 76.05% (Tx Red), and 71.88% (DAPI), respectively. In the TBI model, the ratio of pretreatment to untreated decreased by 56.85% (FITC), 44.28% (Tx Red), and 46.36% (DAPI), respectively. Furthermore, we tested the applicability of the protocol using immunofluorescence staining or Cyanine-5.5 labeling in the three models. SBB treatment is highly effective and can be applied to immunofluorescence and fluorescence label imaging techniques. SBB pretreatment effectively reduced background fluorescence but did not significantly reduce the specific fluorescence signal and greatly improved the signal-to-noise ratio of fluorescence imaging. In conclusion, the optimized SBB pretreatment protocol blocks brain section autofluorescence of the three acute brain injury models.